Improving Students' Mathematical Critical Thinking Abilities Through the Problem Solving Method on the Sequences and Series Course - Dahliana, Dahliana; Marhami, Marhami; Mursalin, Mursalin (International Journal for Educational and Vocational Studies, 2019)
This study aims to determine the improvement of students' mathematical critical thinking abilities through problem solving methods. This study was hold at MAN 3 Bireuen (High School Level) in the 2019/2020 school’s year. The research method was a quasi-experimental study design nonrandomized Pre-test Post-test Control Group Design. The population of the study were all students of Class XI MAN 3 Bireuen with purposive sampling technique. The study sample was to 30 students for the experimental class and 28 students for the control class. The skill increasing was calculated using normalized gain. Data were analyzed using the t test. The results showed that students’ critical thinking skills mathematically taught through problem solving methods is better than students mathematical critical thinking skills taught through conventional learning.